#Fitmom: an experimental investigation of the effect of social media on body dissatisfaction and eating and physical activity intentions, attitudes, and behaviours among postpartum mothers - Lisa Tang; Marika Tiggemann; Jess Haines (BMC, 2022)
Abstract Background Research has shown that body dissatisfaction is higher during the postpartum period compared to other periods of life, and strongly associated with disordered eating behaviours, which can lead to adverse health outcomes. While results from cross-sectional studies suggest that social media may play an important role in body dissatisfaction among postpartum mothers, causal inference is limited due to the observational nature of the existing research. The objective of this study is to experimentally test the effect of body-focused social media on the body dissatisfaction and eating and physical activity intentions, attitudes, and behaviours of postpartum mothers. Methods Postpartum mothers of infants 0-6 months (n = 132) were randomly assigned to view either body-focused social media posts (n = 65), or a control set of infant feeding tips (n = 67). ANCOVA was used to examine differences between the intervention and control group on levels of body dissatisfaction, eating and physical activity intentions, attitudes, and behaviours. There were two follow-up time points, immediately post intervention and 1-month post intervention to measure potential sustained effects of intervention. Results Exposure to body-focused social media posts resulted in higher levels of body dissatisfaction, mean difference 1.54 (p = 0.002); poorer body image, mean difference 0.41 (p = 0.007); eating attitudes, mean difference 2.26 (p = 0.025); and higher levels of restrained eating behaviours, mean difference 0.39 (p < 0.001) among the intervention group post intervention. Mothers in the intervention group also reported higher levels of inspiration to be active, mean difference 0.48 (p = 0.021) post intervention. A sustained effect was found for restrained eating, mean difference 2.03 (p < 0.001) and poorer eating attitude, mean difference 0.29 (p = 0.001) at 1-month follow-up. No sustained effects were found for any other outcomes at 1-month follow-up. Conclusion Social media exposure to body-focused social media posts negatively affect postpartum mothers' body dissatisfaction and health behaviours. Further experimental research that includes an interactive social media component is needed among this population. Trial Registration: NCT05181280, Study ID Number: 054798. Registered 06/01/2022. Retrospectively registered, https://clinicaltrials.gov/ct2/show/NCT05181280 .